Diagnostic Accuracy of Modified Kenneth Jones Scoring Criteria as Screening Tool to Diagnose New Cases of Pulmonary Tuberculosis in Children - Sonia Saleem; Muhammad Naeem; Aneela Shaheen; Shahid Mahmood Sahi; Bint-; Sara Rubab (University of Lahore, 2024)
Objective: To evaluate the effectiveness of the Modified Kenneth Jones Scoring System as a screening tool for diagnosing pulmonary tuberculosis in children. Methodology: A cross sectional study was conductedto assess the symptoms of tuberculosis among 100 pediatric patients with male to female ratio was 67:33. through Modified Kenneth Jones Scoring System (MKJSC) at Gulab Devi Tertiary Care Hospital, Lahore from June-December, 2022. The study included symptoms based on gender, drug usage and microbial load. Patients diagnosed with TB were included in this study to assess the system's effectiveness in identifying specific symptoms and clinical manifestations of TB. This inclusion allowed for a comprehensive evaluation of the MKJSC's diagnostic accuracy and its potential utility in early detection and intervention in pediatric TB cases. The Data was analyzed using SPSS to identify specific symptoms. Results: The Modified Kenneth Jones Criteria diagnosed 65 patients out of 100 with one false positive. The sensitivity for TB detection was 84.2% (95% CI: 73.6% - 91.2%), specificity was 95.8% (95% CI: 76.8% - 99.7%), positive predictive value was 98.4% (95% CI: 90.5% - 99.9%), and negative predictive value was 65.7% (95% CI: 47.7% - 80.3%). Statistical analysis with 5% confidence interval revealed a medium of age of 73 months and a mode of 120 months among patients. While cough prevalence varied, all patients had a history of prolonged fever. Meningeal irritation was observed in 52% of participants and 77% had contact with TB patients. Other findings included malnutrition 50%, pneumonia 48% and BCG screening 24%. Conclusion: The Modified Kenneth Jones Scoring System demonstrated high sensitivity and specificity in detecting tuberculosis, outperforming previous methods. It proves to be an effective tool in resource-limited healthcare settings for diagnosing TB in children.